Impact of Donor, Host, and Surgical Parameters on High Endothelial Cell Density More Than 5 Years after Penetrating Keratoplasty - Sneyers, Albéric; Daas, Loay; Zemova, Elena; Quintin, Adrien; Munteanu, Cristian; Seitz, Berthold (Klinische Monatsblätter für Augenheilkunde, 2024)
Objectives To investigate the correlation between postoperative endothelial cell loss (ECL) and donor, host, and surgical parameters, and to assess the clinical impact of maintaining a high endothelial cell density (ECD) of ≥ 1500 cells/mm2 5 years after penetrating keratoplasty (PKP).Methods This retrospective cohort study included 216 eyes with 5 years of follow-up, of which 94 had annual visits, and who underwent normal-risk elective PKP for noninfectious indications by one corneal microsurgeon (B. S.) between 2009 and 2016.Results Among the 216 eyes, ECL (39.1%) over 5 years postoperative exhibited weak positive correlations with storage solution time (p = 0.024) and postmortem time (p = 0.028), and moderately positively correlations with the preoperative ECD (p < 0.001). The 5-year postoperative ECL differed significantly between in domo-prepared (36.8%) and ex domo donor corneas (46.3%; p = 0.001). In the 94 eyes, no significant differences were found between the two groups for central pupil pachymetry (CCT) and BCVA (p > 0.074). However, CCT increased significantly between 1 and 4 years (p = 0.034) and 1 and 5 years postoperatively (p = 0.012), respectively. BCVA improved significantly at 1 year postoperatively and continued to improve until 2 years postoperatively (p < 0.001).Conclusion The Lions corneal bank Saar-Lor-Lux achieved a significantly reduced ECL (36.8%) over 5 years compared to ex domo donor corneas (46.3%). A weak positive correlation was found between ECL with the storage solution time and the postmortem time, as well as a moderate positive correlation with the preoperative ECD. Although CCT increased significantly over 5 years, BCVA improved significantly from the first to the second postoperative year and remained stable thereafter.
Keywords: endothelial cell loss; endothelial cell density; penetrating keratoplasty; PKP; 5-year follow-up